2004
DOI: 10.1128/jvi.78.20.11030-11039.2004
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Infection Induces Rapamycin-Insensitive Phosphorylation of Downstream Effectors of mTOR Kinase

Abstract: Signaling mediated by the cellular kinase mammalian target of rapamycin (mTOR) activates cap-dependent translation under normal (nonstressed) conditions. However, translation is inhibited by cellular stress responses or rapamycin treatment, which inhibit mTOR kinase activity. We show that during human cytomegalovirus (HCMV) infection, viral protein synthesis and virus production proceed relatively normally when mTOR kinase activity is inhibited due to hypoxic stress or rapamycin treatment. Using rapamycin inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
175
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(194 citation statements)
references
References 26 publications
19
175
0
Order By: Relevance
“…However, a minor portion of 4EBP1 remains hypophosphorylated in infected cells (28), and this is presumably the 4EBP1 that is antagonized by pUL69. It is well established that 4EBP1 is not degraded after HCMV infection (24,29), so it is likely that pUL69 blocks access of 4EBP1 to the m 7 G-cap complex through its contacts with eIF4A1 and PABPC1. Alternatively, the presence of pUL69 in the complex could make 4EBP1 more susceptible to phosphorylation, which would then cause its exclusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, a minor portion of 4EBP1 remains hypophosphorylated in infected cells (28), and this is presumably the 4EBP1 that is antagonized by pUL69. It is well established that 4EBP1 is not degraded after HCMV infection (24,29), so it is likely that pUL69 blocks access of 4EBP1 to the m 7 G-cap complex through its contacts with eIF4A1 and PABPC1. Alternatively, the presence of pUL69 in the complex could make 4EBP1 more susceptible to phosphorylation, which would then cause its exclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme(s) affected appears to be rapamycininsensitive because: (i) in vitro, the phosphorylation of 4E-BP1 by cell extracts that still takes place after treatment of the cells with rapamycin is decreased following activation of p53; and (ii) in vivo, the p53-induced changes and the effects of rapamycin on 4E-BP1 phosphorylation are additive. Some reports have indicated that, under certain circumstances, mTOR can still be active in the presence of rapamycin (Edinger et al, 2003;Kudchodkar et al, 2004;Sarbassov et al, 2004) and it is possible that p53 inhibits such an activity of mTOR. However, there are also other candidates for rapamycin-insensitive protein kinase(s) that may phosphorylate Ser 64 and Thr 69 on 4E-BP1 and that could be inhibited by p53.…”
Section: Discussionmentioning
confidence: 99%
“…Upon binding, HCMV is internalized and initiates typical EGFR signaling, including the activation of PI3K and Akt (Wang et al, 2003a). Subsequently, the phosphorylation of both S6K (Johnson et al, 2001;Andreoni et al, 2002) and 4EBP1 (Kudchodkar et al, 2004) is strongly induced, although one group finds that 4EBP1 is induced independently of PI3K (Kudchodkar et al, 2004). PI3K/Akt activation is especially significant as HCMV replication and viral gene expression is significantly reduced by the PI3K inhibitor LY294002 (Johnson et al, 2001).…”
Section: Viruses and Mtormentioning
confidence: 99%